Beneficial Effects of Capybara Oil Supplementation on Steatosis and Liver Apoptosis in Obese Mice - Luciana Lontro Alves; Priscila Gomes Pereira; Bianca Torres Ciambarella; Miguel Porto Campos; Kíssila Rabelo; Ana Lúcia Rosa Nascimento; Raíssa Leal de Carvalho dos Santos Cunha; Cherley Borba Vieira Andrade; Alan Cesar Nunes Moraes; Andressa Bernardi; Fernanda Verdini Guimarães; Jemima Fuentes Ribeiro da Silva; et al. (Journal of Obesity)
Obesity is a complex chronic disease characterized by excess body fat (adipose) that is harmful to health and has been a major global health problem. It may be associated with several diseases, such as nonalcoholic fatty liver disease (NAFLD). Polyunsaturated fatty acids (PUFA) are lipid mediators that have anti-inflammatory characteristics and can be found in animals and plants, with capybara oil (CO) being a promising source. So, we intend to evaluate the hepatic pathophysiological alterations in C57Bl/6 mice with NAFLD, caused by obesity, and the possible beneficial effects of OC in the treatment of this disease. Eighteen 3-month-old male C57Bl/6 mice received a control or high-fat diet for 18 weeks. From the 15th to the 18th week, the animals received treatment—through orogastric gavage—with placebo or free capybara oil (5 g/kg). Parameters inherent to body mass, glucose tolerance, evaluation of liver enzymes, percentage of hepatic steatosis, oxidative stress, the process of cell death with the apoptotic biomarkers (Bax, Bcl2, and Cytochrome C), and the ultrastructure of hepatocytes were analyzed. Even though the treatment with CO was not able to disassemble the effects on the physiological parameters, it proved to be beneficial in reversing the morphological and ultrastructural damage present in the hepatocytes. Thus, demonstrating that CO has beneficial effects in reducing steatosis and the apoptotic pathway, it is a promising treatment for NAFLD.